1987
DOI: 10.1103/physrevb.35.6107
|View full text |Cite
|
Sign up to set email alerts
|

Moving discommensurations interacting with diffusing impurities

Abstract: We present an analytical description of the interaction between moving discommensurations and diffusing impurities for a realistic form of the impurity-discommensuration interaction energy. This interaction energy is derived within the framework of the modified sine-Gordon model with either misfit impurities (coupling to the gradient of the order parameter) or elastic-modulus impurities (coupling directly to the order parameter). This interaction potential is then employed in calculating the steady-state impur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 12 publications
3
17
0
1
Order By: Relevance
“…The Values Fpi n found in thi8 paper are in agreement with those obtained in [7] equal to 10 -8 Ν for Ba2Νa• Νb5O15 crystals.…”
Section: Influence Of Mechanical Stress On the Birefringence Propertisupporting
confidence: 80%
See 2 more Smart Citations
“…The Values Fpi n found in thi8 paper are in agreement with those obtained in [7] equal to 10 -8 Ν for Ba2Νa• Νb5O15 crystals.…”
Section: Influence Of Mechanical Stress On the Birefringence Propertisupporting
confidence: 80%
“…sults obtained in this paper illustrate a set of hysteresis force-velocity dependences for description of soliton motion under mechanical field influence. Numerical values of Fpi n are in agreement with the theoretical estimation [7]. We suppose analogous behaviour for other IC crystals.…”
Section: Influence Of Mechanical Stress On the Birefringence Propertisupporting
confidence: 77%
See 1 more Smart Citation
“…As one can see, at the absence of the electric field the yo, value smoothly varies with temperature and shows inessential anomalous changes. Electric field of strength E =10 4 V/m applied to the sample results in an anomalous temperature behaviour of φa . The optical indicatrix rotation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that antipolarised regions disappear under influence of electric field and left the vestige, which serves as a germ at field removal. This vestige may be considered as residual defects concentration around soliton [4], that actually causes DDW existence in the crystal. DDW period coincides with the incommensurate structure period at the field absence.…”
Section: Introductionmentioning
confidence: 99%